2020
DOI: 10.1158/1538-7445.am2020-1071
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1071: Targeting A2aR in mouse Pten-deficient prostate cancer

Abstract: Inactivation of PTEN occurs frequently in advanced human prostate cancer and can promote an immunosuppressive tumor microenvironment (TME). Extracellular adenosine can be produced by tumors which can in turn modulate anti-inflammatory and immunosuppressive effects via interactions with the A2a receptor (A2aR). Here, we used a transgenic mouse model of Pten-deficient prostate cancer to characterize adenosine-mediated immunosuppression in the TME and evaluate the effects of A2aR blockade. Transcriptomic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Peripheral levels of PMN‐MDSCs are elevated in patients with mCRPC and are recruited to tumors where they accumulate 144–146 . Hypoxia, which is a hallmark of cancer and is also prevalent in human CRPC, can also increase levels of extracellular adenosine to recruit myeloid cells into tumors 147–150 . In tumors, PMN‐MDSCs produce several suppressive molecules such as IL‐23, TGF‐β, arginase 1, IL‐10, and ROS that dampen effector T‐cell function and induce the expansion of Tregs 145,151 .…”
Section: Immunosuppressive Niches Of the Tme Of Crpcmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral levels of PMN‐MDSCs are elevated in patients with mCRPC and are recruited to tumors where they accumulate 144–146 . Hypoxia, which is a hallmark of cancer and is also prevalent in human CRPC, can also increase levels of extracellular adenosine to recruit myeloid cells into tumors 147–150 . In tumors, PMN‐MDSCs produce several suppressive molecules such as IL‐23, TGF‐β, arginase 1, IL‐10, and ROS that dampen effector T‐cell function and induce the expansion of Tregs 145,151 .…”
Section: Immunosuppressive Niches Of the Tme Of Crpcmentioning
confidence: 99%
“…[144][145][146] Hypoxia, which is a hallmark of cancer and is also prevalent in human CRPC, can also increase levels of extracellular adenosine to recruit myeloid cells into tumors. [147][148][149][150] In tumors, PMN-MDSCs produce several suppressive molecules such as IL-23, TGF-b, arginase 1, IL-10, and ROS that dampen effector T-cell function and induce the expansion of Tregs. 145,151 PMN-MDSCs also inhibit T-cell cytotoxic activity by producing CCL4 and CCL5 to recruit Tregs in tumors.…”
Section: Immunosuppressive Niches Of the Tme Of Crpcmentioning
confidence: 99%
“… 23 AZD4635 has shown antitumor activity (reduction of tumor burden compared with control mice) in PTEN -deficient prostate cancer models showing evidence of immune modulation by extracellular adenosine in prostate cancer. 24 In the phase I study, AZD4635 has demonstrated clinical activity in mCRPC, and appears to have increased efficacy in combination with anti-PD-L1 in mCRPC due to increased immune activation compared with single-agent AZD4635. 25 Taken together, AZD4635 treatment results in a less immunosuppressive TME and may complement other immune-targeting drugs to enhance clinical response.…”
Section: Introductionmentioning
confidence: 99%